Firm Investment and Monetary Policy Transmission in the Euro Area - Ulf von Kalckreuth; Ignacio Hernando; Andrea Generale; Jean Bernard Chatelain; Philip Vermeulen (Deutsche Bundesbank, 2001)
We present a comparable set of results on the monetary transmission channels on firm investment for the four largest euro-area countries (Germany, France, Italy and Spain). With particularly rich micro datasets for each country containing over 215,000 observations from 1985 to 1999, we explore what can be learned about the interest channel and the broad credit channel. For each of those countries, we estimate neoclassical investment relationships, explaining investment by its user cost, sales and cash flow. We find investment to be sensitive to user cost changes in all those four countries. This implies an operative interest channel in these euro-area countries. We also find investment in all countries to be quite sensitive to cash flow movements. However, only in Italy do smaller firms react more to cash flow movements than large firms, implying that a broad credit channel might not be equally pervasive in all countries. – – In einer vergleichenden Betrachtung untersuchen wir die Kanäle monetärer Transmission bezüglich des einzelwirtschaftlichen Investitionsverhaltens in den vier größten Ländern des Euro-Währungsraums (Deutschland, Frankreich, Italien und Spanien). Bei unserer Untersuchung des Zinskanals und des Kreditkanals können wir auf ausgesprochen reiche Datensätze mit insgesamt 215.000 Beobachtungen zurückgreifen. Für jedes dieser Länder schätzen wir neoklassische Investitionsgleichungen, bei denen das Investitionsverhalten durch die Kapitalnutzungskosten, den Absatz und den cash flow erklärt werden. In allen vier Ländern reagiert das Investitionsverhalten auf Änderungen der Kapitalnutzungskosten. Dies zeigt die Wirksamkeit eines Zinskanals in diesen Ländern. Weiterhin erweist sich in allen Ländern der betriebliche cash flow als wichtige Determinante für das Investitionsverhalten. Allerdings reagieren nur in Italien kleine Firmen stärker auf Änderungen des cash flows als große Firmen. Dies läßt darauf schließen, daß der Kreditkanal der monetären Transmission nicht in allen Ländern von gleicher Bedeutung ist.
Keywords: E22; E50; 330; Investition; Monetäre Transmission; Kapitalnutzungskosten; investment; monetary transmission; user cost of capital; Transmissionsmechanismus; Investition; Kapitalkosten; Transmissionsmechanismus; Investition; Kapitalkosten; Deutschland; Frankreich; Italien; Spanien; Deutschland; Frankreich; Italien; Spanien